Associated Factors of the Need for Mechanical Ventilation Following Traumatic Injuries; a Registry-Based Study on 2,708 Cases in Iran - Zahra Ramezani; Vali Baigi; Mohammadreza Zafarghandi; Vafa Rahimi-Movaghar; Reza Farahmand-Rad; Akram Zolfaghari Sadrabad; Seyed-Mohammad Piri; Mahgol Sadat Hassan Zadeh Tabatabaei; Khatereh Naghdi; Payman Salamati (Archives of Academic Emergency Medicine)
Introduction: Traumatic injuries can affect respiration both directly and indirectly. This study aimed to evaluate the predictive factors of need for mechanical ventilation (MV) following traumatic injuries.